2018
DOI: 10.1021/acs.energyfuels.8b00074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Size Distribution on Dissociation Temperature Depression and Phase Boundary Shift of Gas Hydrate in Various Fine-Grained Sediments

Abstract: Capillarity in small, confined pores has a pronounced effect on the depression of the dissociation temperature of gas hydrates, known as the Gibbs–Thomson effect. However, this effect remains poorly understood in natural fine-grained sediments with wide pore size distributions. This study investigated the effect of pore size distributions of fine-grained sediments on the dissociation temperature of a gas hydrate. A gas hydrate was synthesized under partially water-saturated conditions in nanosized silica gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…The depression of the gas hydrate dissociation temperature with decreasing pore size has been observed by several researchers. 16,17,23 It was observed that there is a shift in gas hydrates dissociation temperature when the pore size is between 3 and 100 nm. Additionally, Nath et al showed using Monte Carlo simulations of methane hydrates in confinement of various pore sizes (using TIP4P and TIP4P/2005 models), a depression in hydrate dissociation temperature of up to around 28 K for 5 nm pore diameter.…”
Section: Effect Of Pore Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The depression of the gas hydrate dissociation temperature with decreasing pore size has been observed by several researchers. 16,17,23 It was observed that there is a shift in gas hydrates dissociation temperature when the pore size is between 3 and 100 nm. Additionally, Nath et al showed using Monte Carlo simulations of methane hydrates in confinement of various pore sizes (using TIP4P and TIP4P/2005 models), a depression in hydrate dissociation temperature of up to around 28 K for 5 nm pore diameter.…”
Section: Effect Of Pore Sizementioning
confidence: 99%
“…The depression of the gas hydrate dissociation temperature with decreasing pore size has been observed by several researchers. 16,17,23 It was observed that there is a shift in gas hydrates dissociation temperature when the pore size is between 3 and 100 nm. Additionally,…”
mentioning
confidence: 99%
“…Significant downward shifts of the dissociation temperature were observed in porous glass [36]. The melting temperature depression and the shifted phase boundaries were monitored [37]. The methane hydrate heat of dissociation into pore water and gas in 7-nm-radius silica gel pores, obtained calorimetrically, was 45.92 kJ/mol [38].…”
Section: Introductionmentioning
confidence: 99%
“…By studying the mass transfer of these processes, we can explore the control mechanism of hydrate accumulation and mining. Experimental results have shown the relationship between nanoscale pores bearing gas hydrates and dissociation behavior [36][37][38]. The dissociation conditions of methane hydrates in confined small pores were measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation